2008
DOI: 10.1097/gim.0b013e3181616bf8
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment of routine nuchal translucency measurements: a North American laboratory perspective

Abstract: Purpose: To assess nuchal translucency measurements that were performed as part of routine prenatal screening for Down syndrome. Methods: Collect ultrasound measurements of nuchal translucency and crown rump length provided by individual sonographers over a 6-month period to six North American prenatal screening laboratories, along with the laboratory's nuchal translucency interpretation in multiples of the median. For sonographers with 50 or more observations, compute three nuchal translucency quality measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 27 publications
(46 reference statements)
3
53
0
4
Order By: Relevance
“…41 Target ranges for the three parameters are (1) 15% to 35%, (2) 0.90 to 1.10 MoM, and (3) standard deviations of 0.08 to 0.13. 65 Neither the percent per week increase nor logarithmic standard deviation are under the direct control of the screening laboratory. However, the laboratory can adjust the median values when the median MoM for a given sonographer is outside of the expected range.…”
Section: Performance Guidelines For Qa/epidemiological Monitoring Metmentioning
confidence: 99%
“…41 Target ranges for the three parameters are (1) 15% to 35%, (2) 0.90 to 1.10 MoM, and (3) standard deviations of 0.08 to 0.13. 65 Neither the percent per week increase nor logarithmic standard deviation are under the direct control of the screening laboratory. However, the laboratory can adjust the median values when the median MoM for a given sonographer is outside of the expected range.…”
Section: Performance Guidelines For Qa/epidemiological Monitoring Metmentioning
confidence: 99%
“…Die vorgeburtliche Risikoabklärung insgesamt sowie jede einzelne ihrer Komponenten (Ultraschall, laboratoriumsmedizinische Untersuchungen, Algorithmus) müssen einer kontinuierlichen Qualitätssicherung unterzogen werden. Durch eine kontinuierliche Qualitätssicherung kann das Problem der Unterschätzung der Nackentransparenz deutlich verringert und so die Entdeckungsrate erhöht werden [17,18,19]. Eine externe Qualitätssicherung ist insbesondere für den Bereich Ultraschall wesentlich, weil es sich bei der fetalen Nackentransparenz um eine Messung im Bereich um 0,1 mm handelt und deren Genauigkeit direkt von der Qualifikation des Anwenders abhängt [17].…”
Section: Begründungunclassified
“…The UKNSP estimated that a deviation of 10% on a serum markers MoM was sufficient to change the screen positive rates by approximately 2% [8]. Assessment of NT scan quality at a single laboratory, however, indicated that only 55% of the 140 sonographers who had performed 50 or more scans within a 6 month period had NT measurement distributions whose median were within 10% of the expected values [9]. The recent study by Kagan et al demonstrated the effects of departures from the expected NT distribution on DRs and FPRs [10].…”
Section: Introductionmentioning
confidence: 97%